In vitro effect of caffeic acid phenethyl ester on matrix metalloproteinases (MMP-1 and MMP-9) and their inhibitor (TIMP-1) in lipopolysaccharide-activated human monocytes - Vilela, Polyana das Graças Figueiredo [UNESP]; Oliveira, Jonatas Rafael de [UNESP]; Barros, Patrícia Pimentel de [UNESP]; Leão, Mariella Vieira Pereira; Oliveira, Luciane Dias de [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP] (Elsevier B. V., 2015)
The role of matrix metalloproteinases (MMPs) in tissue degradation has become evident in many diseases and great interest therefore exists in the pharmacological control of the activity of these enzymes. This study evaluated the effect of caffeic acid phenethyl ester (CAPE) on the production of MMPs and their inhibitor (TIMP) in monocytes activated by lipopolysaccharide (LPS). The human monocytic cell line (THP-1) was treated with non-cytotoxic concentrations of CAPE (10 and 60μM) combined with 1μg/mL of LPS. The gene expression of MMP-1, MMP-9 and TIMP-1 was evaluated by quantitative real-time polymerase chain reaction. The protein secretion into the culture medium was assessed via enzyme-linked immunosorbent assay and the gelatinolytic activity of MMP-9 by zymography. CAPE, especially at the highest concentration, down-regulated MMP-1 and MMP-9 gene expression but up-regulated the gene expression of TIMP-1. Furthermore, CAPE reduced the secreted protein level of MMP-1 and MMP-9 as well as the gelatinolytic activity of MMP-9. CAPE was able to inhibit the gene expression, production and the activity of MMPs induced by LPS and also increased the gene expression of TIMP-1. The present observations suggest that CAPE exerted a positive effect on the regulatory mechanism between MMPs and TIMP, which is important for the control of different diseases.
Keywords: Cape; Lipopolysaccharide; Matrix metalloproteinases; Monocytes